Rol de enfermería en la promoción de hábitos de salud destinados a prevenir la hipertensión arterial en usuario 50 - 65 años al Subcentro los Ángeles. octubre 2018/abril 2019 - Morante Mora, Yury Vanessa (2019)
Hypertension is the main cause of death in the world in recent times is considered a condition that constitutes a public health problem country people percentages, nursing is oriented to providing care for attention and in the health promotion teaching acquired knowledge and apply them to users for prevention in hypertension. The objective is to determine the role of professional nursing in the promotion of healthy habits that affect high blood pressure of adults whose age is from 50 to 65 years who come to care Health Center in los Angeles, in the methodology used e s inductive method allows to recognize the variables and the deductive method enables to achieve conclusions research was conducted it with a quantitative approach descriptive addition is crosscutting, with a population of 307 and the sample of 62 users from 50 to 65 years who attends the sub-centre with an average of 75% are of this age, being 60% of the rural areas, the technique used for the obtaining of data is the survey the instrument of data collection consisted of a form drawn up based on the variable object of study, information offering the nursing staff is unsatisfactory 56% and on information received about the care is by pate of the doctor.